OPTIMASI PRODUKSI DAN PENGENDALIAN BAHAN BAKU STUDI KASUS PADA PT. JOSHUA INDO EXPORT - Susanto, Tedy; Sarwadi, Sarwadi (MATEMATIKA, 2006)
Production optimization and inventory control on raw materials are among the main problem in companyâ€™s management. These two issues are the subjets of this article. This article is a case study on a furniture exporter company PT.Joshua Indo Export, where the data was collected. The aim of this article is to compare the policy in the production and inventory control on raw materials in the company with the one which is the result of its optimization. We use Economic Order Quantity (EOQ) model to optimize the production and inventory control on raw materials in the company. The computation and the analysis produce a policy which show that there are some saving in the cost of production and the inventory compared with the currently implemented policy. Â